2020
DOI: 10.1563/aaid-joi-d-19-00130
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Implant Stability Between Two Noninvasive Methods Using Submerged and Nonsubmerged Healing Protocols: A Randomized Clinical Trial

Abstract: Various invasive and non-invasive methods have been used for measuring primary implant stability. Periotest damping device, and resonance frequency analysis (RFA) with the Osstell device have been classified as non-invasive methods.In this clinical randomized trial, a general correlation of primary implant stability was recorded using both the Osstell and Periotest device at the day of implant installation and 3 month after healing for the submerged and non submerged   loading protocols. The gender of included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…At the day of implant installation, patients were randomized using sealed envelopes into two groups: nonsubmerged (NS) and submerged (S); a 3-month healing period was allowed for all patients in both groups. The present study has followed the same inclusion criteria, sample size calculation, and all of the clinical relevant procedures as the trail performed by AAl et al 25 All included patients (age range: 50–69 years) were recruited following strict inclusion criteria: patients with glycosylated hemoglobin level ≥8, patients seeking to install a single median implant in the mandible, and for whom new dentures will be constructed were included. Patients with any condition that would contraindicate implant placement were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…At the day of implant installation, patients were randomized using sealed envelopes into two groups: nonsubmerged (NS) and submerged (S); a 3-month healing period was allowed for all patients in both groups. The present study has followed the same inclusion criteria, sample size calculation, and all of the clinical relevant procedures as the trail performed by AAl et al 25 All included patients (age range: 50–69 years) were recruited following strict inclusion criteria: patients with glycosylated hemoglobin level ≥8, patients seeking to install a single median implant in the mandible, and for whom new dentures will be constructed were included. Patients with any condition that would contraindicate implant placement were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…At the day of implant installation, patients were randomized using sealed envelopes into two groups, nonsubmerged (NS) and submerged (S), and a 3-month healing period was allowed for all patients in both groups. The present study has followed the same inclusion criteria, sample size calculation, and all of the clinical relevant procedures of the trail carried out by Aal et al [ 35 ]. All included patients (age ranging from 50–69 years) were recruited following strict inclusion criteria: glycosylated hemoglobin level ≥ 8, patients seeking to install a single median implant in the mandible, and for whom new dentures will be constructed were included.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported a correlation between RFA and DCA device values, indicating the stability of the same implant. 16 17 18 19 20 In vitro studies showed a strong correlation (more than 0.7) between RFA and DCA devices. 16 19 20 Lee et al 16 showed a correlation coefficient of 0.981 with statistical significance between the ISQ and implant stability tester (IST; Anycheck) values; Krafft et al 19 also reported a correlation coefficient of 0.871 with statistical significance between ISQ and PTV.…”
Section: Introductionmentioning
confidence: 98%
“…Andreotti et al 17 reported a correlation coefficient of 0.294 between ISQ value and PTV with statistical significance through a systematic review. Aal et al 18 showed that when correlating ISQ value and PTV readings of the buccal surface during implant installation, there was a moderate negative statistically significant correlation (correlation coefficient:-0.466) between the two devices for all 80 patients in a clinical trial. The different results between the experimental and clinical conditions suggest that there are factors in clinical conditions that affect the reliability of implant stability measuring devices.…”
Section: Introductionmentioning
confidence: 99%